Premature mortality patterns among American Indians in North Dakota, 2010–2019 (pre-pandemic) - Nadeau, Melanie; Steele, Joel S.; Lyon-Colbert, Amber; Kelliher, Allison; Barnett, Joshua; Begay, Andria; Warne, Donald (Frontiers in Public Health, 2025)
BackgroundAccording to the National Center for Health Data, in 2017 American Indians in North Dakota experience the highest age-adjusted mortality rate in the United States. Data shows that the age-adjusted death rate for all North Dakotans has steadily declined since 1979. However, mortality remains high among American Indians in North Dakota.PurposeAssess pre-pandemic disparities and age-specific mortality patterns to better inform and guide communities and providers on prevention, planning, and policy efforts to advance health equity.MethodsDeath certificate data from 2010–2019 were obtained and analyzed, evaluating the decade prior to the COVID-19 pandemic in order to assess pre-pandemic age-specific mortality rates and rate ratios for 3,369 American Indian and 57,778 White residents in North Dakota. Premature mortality is defined as death <65 years of age.ResultsThe median age at death for American Indian males in North Dakota from 2010 to 2019 was 55 compared to 77 years for White males, and the median age at death for American Indian females was 62 compared to 85 years for White females. Consistent patterns for leading causes of death showed that American Indians suffer disproportionately compared to White residents in North Dakota. The three leading causes of death for American Indians in North Dakota, accounting for approximately 55.4% of all deaths were diseases of the heart (21.7%), cancer (18.5%), and accidents (15.2%). From 2010 to 2019, all cause mortality rates were higher in every age and sex stratum for American Indians compared to White residents in North Dakota. American Indians die 22.5 years younger on average compared to White residents in North Dakota starting at birth and continuing over the lifespan.ConclusionTo best address the health and wellbeing of the American Indian population in North Dakota, multisectoral efforts focused on prevention, improved policies, and cultural humility and safety in the health systems are needed. Solutions should center American Indian voices, cultures and spaces, and include Tribes, Tribal organizations, Tribal health, Indian Health Service and Urban Indian Health Centers. Additionally, standards for death certificates in the United States could benefit populations by accurately reflecting race and rates of illness and death.